Solusi Numerik Model Matematika Pada Kasus Kecanduan Media Sosial Tiktok Di Pondok Pesantren Annuqayah Latee II Menggunakan Metode Runge Kutta - Siti Romlah; Muhammad Thahiruddin; Luluk Sarifah (Alpha-Epsilon: Journal of Mathematics, 2025)
TikTok social media is a medium that can develop users' creativity, but most users compete to express themselves due to frequently viewing content so that they are obsessed with creating content and continuously trying various content movements. This can result in an addiction to viewing or addiction to TikTok content movements. Modifying the TikTok social media addiction model is one of the objectives of this research, starting by distributing a questionnaire to 100 respondents. Next, a programming simulation was carried out using the Runge Kutta Butcher method with Python tools. With the results, the Runge Kutta Butcher method can provide high accuracy and is effective in solving the SEIIRS model. The population increased with an increase of 18 individuals exposed, indicating the possibility of movement of susceptible individuals. The decline in infected populations 1 and 2 shows that individuals in these populations are slowly becoming recovered individuals. Based on the findings of this research, it can be concluded that Santri PP Annuqayah Latee II had previously experienced TikTok addiction and would return to normal status (cured but vulnerable) on Day 200.